Chemically leavened gluten free sorghum bread - Ari Akin, Pervin (Kansas State University, 2017)
Sorghum is unique in terms of its resistance to drought and heat and is grown and consumed around the globe. Moreover, sorghum does not contain gluten and has potential in the gluten-free market. A blend of non-wheat flour, starch and hydrocolloid typically provide the structure of gluten-free products. Most research on sorghum bread uses a yeast leavened process, HPMC gum, rice flour and corn, potato, or tapioca starch. Little is known about the functionality or interactions of different starches and hydrocolloids in sorghum batter. The objectives of this study were to examine starch-hydrocolloid interaction in chemically leavened gluten free sorghum bread; to evaluate the effects of different ingredients on gluten free bread quality made with sorghum flour: starch (tapioca starch, rice flour and potato starch): hydrocolloid (HPMC, locust bean gum and xanthan) and to develop a chemically leavened gluten free sorghum bread method. Bread was baked as pup loaves. Volume index was measured using the AACCI Method 10-91.01 template, crumb grain was evaluated using the C-Cell Imaging System and texture was determined with the TA.XT Plus Texture Analyzer. The base formula was commercial sorghum flour, water, starch, hydrocolloid, sugar, salt, shortening and double acting baking powder. Sorghum flour: starch (tapioca starch, rice flour and potato starch) ratios of 70:30, 80:20 and 90:10 were tested. Loaves containing all levels of rice flour had the same volume index (~165) as 100% sorghum flour (168) while all levels of tapioca starch and potato starch produced significantly smaller loaves (~150). The ratio of 90% sorghum flour and 10% starch (tapioca starch, rice flour and potato starch) was selected. The type and level of hydrocolloid significantly impacted loaf volume, grain and texture. Starch-hydrocolloid combinations which produced the best loaves were tapioca starch + 3% HPMC, rice flour + 3% xanthan and potato starch + 4% xanthan. Following initial optimization experiment, egg ingredients, fat, baking powder and water were added and evaluated individually to develop an optimized formulation. In general, addition of egg ingredients, shortening and oil did not improve the overall quality of sorghum based bread and were not added to the formula. However, emulsified shortening was effective. The best level of emulsified shortening was determined to be 3% for the breads with sorghum flour: tapioca starch or sorghum flour: potato starch and 5% for bread made with sorghum flour: rice flour. The best baking powder (SALP and MCP) levels were 5, 8 and 5% for sorghum flour: tapioca starch bread, sorghum flour: rice flour bread and sorghum flour: potato starch bread, respectively. Optimum levels of water for sorghum flour: tapioca starch bread, sorghum flour: rice flour bread, and sorghum flour: potato starch bread were 120, 110 and 120%, respectively. This research showed that different starch sources have different interactions with other ingredients in chemically leavened sorghum based gluten free bread.
Keywords: Sorghum; Starch; Hydrocolloid; Gluten-free; Bread